EFEKTIVITAS DAYA HAMBAT EKSTRAK ETANOL DAGING BUAH PALA (MYRISTICA FRAGRANS) TERHADAP PERTUMBUHAN CANDIDA ALBICANS SECARA IN VITRO - Galih Sihwianti (2021)
Candida albicans is the most common etiology of candidiasis. Candidiasis can infect both the superficial and systemic. Candidiasis affects 90% of patients infected with HIV/AIDS. The widespread use of fluconazole in curative and preventive therapy has been reported to cause an increased incidence of resistance to C. albicans. Nutmeg flesh (Myristica fragrans) is an underused part of the plant compared to seeds and mace. Nutmeg contains active compounds of alkaloids, saponins, tannins, flavonoids, and terpenoids. Terpenoid considered affect the most in the extract inhibition capability, because their antifungal mechanism can inhibit cell wall pectin methylesterase, alter fatty acid membrane structure, and inhibit fungal cell cycle. The aimed of this research is to determine the inhibition ability of nutmeg flesh extract on the growth of C. albicans. This research is an experimental study using a post test only control group design, using concentrations extract 5%, 10%, 25%, 50%, 75%, and 100%. The test using well diffusion method on Saboraud Dextrose Agar which was incubated for 24, 48, and 72 hours The data analyzed using One-Way ANOVA or Kruskal-Wallis test with p value=0.00 on each incubation time, which shows significant difference outcome between nutmeg flesh extract and inhibitory zone of C. albicans. The inhibition zone at concentration 50,%, 75%, and 100% are increasing, while the inhibition zone at concentration 5%, 10%, and 25% are decreasing. The extract concentration 50% is the most effective because there is no significant difference of the inhibitory zone from concentration 75% in 24 and 48 hour incubation time and it belongs to strong inhibition response category.